The determinants of IPOs and Reverse mergers: Chinese companies listed in Hong Kong - XIANG, YANG (2010)
The idea of this study is to identify the determinants of an IPO and a RM in Hong Kong stock market. In this study, we use 50 Chinese companies listing in Hong Kong to find out the determinants. Seven independent variables are adopted in the study, including firm size, age, performance, profitability, costs of IPO or RM, growth opportunities and hot market dummy. Analysis shows that smaller, poorer performing and younger Chinese companies choose a RM rather than an IPO. RM firms met at least one of the listing standards while the IPOs met most of the initial listing requirements in Hong Kong stock market.